2016
DOI: 10.1002/eji.201646536
|View full text |Cite
|
Sign up to set email alerts
|

1‐Fluoro‐2,4‐dinitrobenzene and its derivatives act as secretagogues on rodent mast cells

Abstract: Accumulating evidence suggests that activated mast cells are involved in contact hypersensitivity, although the precise mechanisms of their activation are still not completely understood. We investigated the potential of common experimental allergens to induce mast cell activation using murine bone marrow-derived cultured mast cells and rat peritoneal mast cells. Among these allergens, 1-chloro-2,4-dinitrobenzene and 1-fluoro-2,4-dinirobenzene (DNFB) were found to induce degranulation of rat peritoneal mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Indeed, Dudeck et al reported MC degranulation in skin sections obtained 4 h after sensitization with DNFB ( 59 ). A recent report also shows that DNFB, but not oxazolone, can induce direct degranulation of rat PMCs in vitro ( 74 ). MC activation has been best visualized in the effector phase using two-photon microscopy.…”
Section: Potential Mechanisms Of MC Activation In Chsmentioning
confidence: 93%
“…Indeed, Dudeck et al reported MC degranulation in skin sections obtained 4 h after sensitization with DNFB ( 59 ). A recent report also shows that DNFB, but not oxazolone, can induce direct degranulation of rat PMCs in vitro ( 74 ). MC activation has been best visualized in the effector phase using two-photon microscopy.…”
Section: Potential Mechanisms Of MC Activation In Chsmentioning
confidence: 93%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11060953/s1, Figure S1: The inhibitors employed in main Figure 1 exert no cytotoxicity on cultured skin MC; Figure S2: MC degranulation via MRGPRX2 relies on Gαi, Gαq and calcium mobilization as evidenced by histamine release; Figure S3: The survival of ex vivo skin MC is not perceptibly compromised by the inhibitors employed in main Figure 1; Figure S4: Differences between c48/80 and SP from main Figure 1; Figure S5: Comparison between cultured and ex vivo skin MCs from main Figure 1; Figure S6: The inhibitors employed in main Figure 2 exert no cytotoxicity on cultured skin MC; Figure S7: The survival of ex vivo skin MCs is not perceptibly compromised by the inhibitors employed in main Figure 2; Figure S8: Differences between c48/80 and SP from main Figure 2; S1: Inhibitors employed and their primary targets. References [15,30,31,33,36,38,39,44,49,51,55,[60][61][62][86][87][88][89][90][91][92][93][94][95][96] are cited in the Supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…ERK Activation by H4R in Spinal Cord Underline Chronic Itch serum proteins and IgE (Manabe et al, 2017). We also used an in vitro immunohistochemistry method to further demonstrate that DNFB, histamine, and H4R agonist 4methylhistamine are all sufficient to induce ERK activation in spinal cord neurons.…”
Section: Discussionmentioning
confidence: 92%